2013
DOI: 10.4236/health.2013.58a2005
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality, sleep patterns and consumption of energy drinks and other caffeinated beverages among Peruvian college students

Abstract: Objectives To evaluate sleep quality in relation to lifestyle characteristics including consumption of energy drinks and other caffeinated beverages among Peruvian college students. Methods A total of 2,458 college students were invited to complete a self-administered questionnaire that collected information about a variety of behaviors including consumption of energy drinks, caffeinated and alcoholic beverages. The Pittsburgh Sleep Quality Index (PSQI) was used to assess sleep quality. Logistic regression p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
39
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 26 publications
9
39
2
2
Order By: Relevance
“…This result agrees with the findings of Sanchez et al [30] in their study done among Students from Peruvian College (Peru). In the current study, students who took a daytime naps had a higher percentage of poor sleep quality compared to others, but without statistical significant difference.…”
Section: Discussionsupporting
confidence: 93%
“…This result agrees with the findings of Sanchez et al [30] in their study done among Students from Peruvian College (Peru). In the current study, students who took a daytime naps had a higher percentage of poor sleep quality compared to others, but without statistical significant difference.…”
Section: Discussionsupporting
confidence: 93%
“…This classification system is consistent with prior studies conducted globally including Peru. 31,32 We have demonstrated that the Spanish-language version of the PSQI instrument to have good construct validity among pregnant women in Peru. 33 …”
Section: Pittsburgh Sleep Quality Index (Psqi)mentioning
confidence: 90%
“…[1][2][3] In a recent multi-country sleep study, high levels of poor sleep quality were reported among Peruvian, Thai, Ethiopian, and Chilean university students. [4][5][6][7] Each of the populations studied showed associations between poor sleep and the consumption of stimulant beverages. [4][5][6][7] Taylor and Bramoweth 8 found that 60% of university-age students reported consuming stimulant beverages (e.g., sodas and coffee) to combat daytime sleepiness.…”
mentioning
confidence: 99%
“…[4][5][6][7] Each of the populations studied showed associations between poor sleep and the consumption of stimulant beverages. [4][5][6][7] Taylor and Bramoweth 8 found that 60% of university-age students reported consuming stimulant beverages (e.g., sodas and coffee) to combat daytime sleepiness. 8 Approximately 96% of Peruvian medical students reported regular consumption of caffeinated drinks, 9 and 34% of them reported using energy drinks.…”
mentioning
confidence: 99%
See 1 more Smart Citation